2019
DOI: 10.1017/s1368980019002088
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality of Japanese adults with respect to age, sex, and income level in the National Health and Nutrition Survey, Japan

Abstract: Objective:Although several studies in Western countries show that higher socioeconomic status is associated with higher diet quality, no study has observed this association in Japan. In the current study, we examined the association between diet quality and the combinations of age, sex, and household income, and also compared the dietary intake between diet quality levels according to household income.Design:Cross-sectional study.Setting:National Health and Nutrition Survey, Japan in 2014.Participants:2785 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
0
19
1
2
Order By: Relevance
“…However, in another study, no associations were found between those variables [64]. Although older age has been related to higher diet quality [65], in the current study, older workers had lower mean diet quality scores. Possible reasons for this finding could be that appetite and sensory abilities diminish with age [66].…”
Section: Discussioncontrasting
confidence: 84%
“…However, in another study, no associations were found between those variables [64]. Although older age has been related to higher diet quality [65], in the current study, older workers had lower mean diet quality scores. Possible reasons for this finding could be that appetite and sensory abilities diminish with age [66].…”
Section: Discussioncontrasting
confidence: 84%
“…The US National Health and Nutrition Examination Survey reported higher adherence to the Dietary Guidelines for the Americans among adults with a higher income [ 52 ]. Similarly, the Japanese National Health and Nutrition Survey conducted in 2014 reported that low-income individuals with a low-quality diet were less likely to meet the Japanese dietary guidelines than higher-income individuals [ 53 ]. In most countries, diet quality was directly associated with SES.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, regarding favorable changes, the frequency of breakfast, a well-balanced diet, and the habit of eating three meals at a given time a day increased, and these changes led to an increase in main-meal frequency. Participants with extended at-home hours reported an increase in vegetable, fruit, and dairy-product consumption, which are low in poor-quality diets [ 24 ]. Previous studies showed that favorable dietary changes are associated with previously poor everyday dietary quality [ 21 ], and staying at home may have resulted in dietary improvement among individuals with poor-quality diets.…”
Section: Discussionmentioning
confidence: 99%